Linking objective and subjective job demands and resources in the JD-R model: A multilevel design - Li, Yiqiong; Tuckey, Michelle R.; Bakker, Arnold; Chen, Peter Y.; Dollard, Maureen F. (Work and stress, 2023)
The Job Demands-Resources (JD-R) model is a well-recognized theoretical framework assessing the impact of job demands and resources on well-being. Though the model conceptualises job demands and resources in terms of how jobs are both objectively designed and subjectively experienced, most studies have relied only on subjective self-reported data. In a comprehensive test of the model, our study investigates how objective job characteristics at the occupation level are associated with employees' perceptions of job demands and resources in their role, and examines the indirect effect of objective characteristics on employee outcomes via perceived characteristics. Multilevel analyses of multisource and lagged data from 2,049 employees in 97 jobs indicated that perceived job characteristics mediate the effects of objective job characteristics on employee outcomes. Specifically, the objective requirement for positive emotional displays is positively related to exhaustion through perceived emotional demands. Second, objective job hazard exposure is positively related to physical health problems through perceived physical demands. Finally, objective job complexity has a significant positive indirect relationship with work engagement through perceived skill discretion. The results suggest that risk identification and enrichment processes should consider the nature of the job itself instead of merely focusing on employees' cognitive appraisals.